ENTERPRISE MANAGEMENT MECHANISM: CONCEPTUAL ASPECTS - Андрусів, Уляна Ярославівна; Зелінська, Галина; Штогрин , Маряна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2021)
The article is devoted to the issue of the mechanism of enterprise management. A review of the literature provided an opportunity to talk about the importance of the issue among scholars, both domestic and foreign. Emphasis is placed on the fact that the mechanism of effective enterprise management must take into account the state of development of the enterprise today in order to adapt it to the new conditions of labor organization due to the spread of coronavirus infection among the population. It is determined that in order to be successful the company had to be only effective, to achieve goals, objectives, indicators, you also need to be effective – to constantly find the best, most progressive tools and management methods to achieve their goals. It was found that there is no consensus among scientists on the definition of the management mechanism, and therefore there is a need to improve the conceptual and terminological apparatus of this concept. It is determined that the basic elements of management are the system, processes, management decisions and personnel. The latter takes precedence over other controls. Signs of efficiency of the control system are determined. Attention is drawn to the fact that the company, as a socio-economic open and dynamic system, can function successfully in market conditions due to well-established management. It is determined that the mechanism implements management decisions, performing the functions of the organization through management processes within the system through the staff of the organization. It is determined that the management of an industrial enterprise reflects the whole set of interrelated processes of planning, organization, motivation and control, which ensure the implementation of the strategy of its innovative development. Emphasis is placed on the fact that to increase the efficiency of the management mechanism of the enterprise, it is advisable to use such modern management technologies as: reengineering, benchmarking, foresight, outsourcing and controlling. At the same time, personnel management technologies such as crowdfunding, teleworking, outsourcing, leasing, etc. should be considered.